ADAPTIVE DIGITAL FILTERING OF AUTOREGRESSION PROCESS DISTORTED BY WHITE NOISE - Azarskov, V. N.; Zhitetskin, L. S.; Stetsenko, N. V. (Problems of Informatization and Management, 2021)
Within the framework of the adaptive approach based on the use of extended OLS, a digital filter is constructed to select a random useful signal, which is described by a first-order autoregressive model with unknown parameters, against a background of discrete white noise. To solve this problem, a procedure for estimating the variance of white noise generating a useful signal is proposed.